Dural ectopic lymphatic structures accumulate during aging and exhibit dysregulation in neurodegenerative diseases - Amit Fruitman Davidi; Sophie Shirenova; Dolev Michaelovich; Giulio Benedetti; Hadar Shtrasberg; Irit Shoval; Hagit Hauschner; Gal Oz; Karin Vardy; Tamir Hirsh; Ravit Madar; Edward A. Stern; et al. (Proceedings of the National Academy of Sciences, 2025)
The meninges serve as a critical interface between the peripheral immune system and the central nervous system, playing a crucial role in maintaining parenchymal homeostasis. Neurodegenerative disorders, such as amyloidosis and tauopathies, are marked by the accumulation of extracellular neurotoxic amyloid-β (Aβ) plaques and intracellular tau tangles, respectively, leading to neuronal cell death and cognitive decline. The role of the adaptive immune response in these pathologies remains under debate. Adaptive immune cells can manifest as ectopic lymphoid structures (ELS), which resemble secondary lymphoid organs, and form at sites of inflammation or pathology. While ELSs can support immune responses against infections or tumors, they may also have detrimental effects in certain pathological conditions. To explore whether meningeal ELS are implicated in aging and neurodegeneration, we analyzed the meninges of aged wild-type mice and mouse models of early-onset Alzheimer’s disease, tauopathy, and Down syndrome-related neurodegenerative disorders. Our findings suggest that the accumulation of dural ELS varies according to age, brain pathology, and sex. Meningeal myeloid cells may contribute to the initiation and maintenance of ELS during aging. These results demonstrate the potential contribution of meningeal ELS to healthy aging and neurodegenerative conditions, offering directions for future research.